Evaluation of improving the quality of drinking water using phosphates on the example of PWiK - Piechurski, Florian (Instal, 2020)
In these networks, the phenomena of pressure loss pollution are observed, hence the need for high water consumption for frequent flushing. The purpose of the research was to indicate the effects of phosphate corrosion inhibitors introduced into the water supply system, supporting the purification process and improving quality as well as preventing secondary water pollution. The research was carried out in 2017-2019 at four points of the water supply network. Analysis of the obtained test results and observations of the rinsing process show that the purification process is carried out correctly. We save water and reduce the costs associated with replacing corroded pipes or their renovation. The consumption of electricity needed to maintain the required water pressure in the network is also reduced, which also reduces its failure rate. For the recipient of water, a noticeable effect of these activities is the removal of its secondary colouring (rust-brown waters due to the presence of iron and manganese) and sediments arising from faucets. The process of dosing of phosphate corrosion inhibitors prevents the formation of biofilm on the walls of the network pipe as well as water supply installations, which are the environment for the development of microorganisms.